Effect of CO2 inhibition on biogenic isoprene emission: Implications for air quality under 2000 to 2050 changes in climate, vegetation, and land use. Issue 13 (9th July 2013) - Tai, Amos P. K.; Mickley, Loretta J.; Heald, Colette L.; Wu, Shiliang
Abstract [1] The inhibition of biogenic isoprene emission by elevated CO2 as observed in many plant taxa may significantly alter the sensitivity of air quality to global changes. We use a one‐way coupled modeling framework to perform simulations under various combinations of 2000 to 2050 changes in climate, natural vegetation, anthropogenic emissions and land use to examine the effect of the CO2‐isoprene interaction on atmospheric composition. We find that consideration of CO2 inhibition substantially reduces the sensitivity of surface ozone and secondary organic aerosol (SOA) to climate and natural vegetation, resulting in much smaller ozone and SOA increases in major populated regions than are projected by previous studies. The impact of land use on air quality is relatively insensitive to CO2 inhibition, rendering land use change the key factor that can offset or enhance the effects of anthropogenic emissions and shape air quality and climate‐relevant species in the mid‐21st century.